Role of Tal1 in murine blood vessel development - Fritzsche, M (2015)
Detailed knowledge about the mechanisms involved in vascular establishment, differentiation and growth is essential to develop new therapies to treat blood vessel formation related conditions like cancer and blinding eye diseases. Although research has investigated the cellular mechanisms of vessel growth in great detail, a clear understanding of the integration of extracellular signals into the transcriptional programme regulating blood vessel formation still remains elusive. In this thesis the role of the transcription factor Tal1 as a regulator of blood vessel formation and differentiation is investigated. Tal1 is a master regulator of embryonic haematopoiesis, adult megakaryopoiesis, and erythrocyte maturation. Tal1 depleted mice die at gestational day E9.5 due to a complete lack of blood. However, several lines of evidence also suggest an important function of Tal1 in blood vessel development. I chose an inducible, endothelial-specific knock-out strategy to investigate the effects of Tal1 depletion in mice with a focus on vascular development. A distinct time window during embryogenesis, in which Tal1 is required for the proper formation of the primitive intra-embryonic vascular network and the dorsal aorta, was identified. In contrast, I demonstrate that there is no requirement of Tal1 for postnatal sprouting angiogenesis or blood vessel homeostasis. This suggests an important role in vasculogenesis rather than angiogenesis and is in line with recent findings which attribute the proper differentiation of endothelial cells to Tal1. In addition, I have generated and characterised transgenic mouse lines in which Cre recombinase activity is controlled by a Dll4 promoter/enhancer construct. Thereby, Cre expression is specifically directed to the arterial endothelium. I believe that this model can be of great interest for angiogenesis research in general and especially for the understanding of induction and maintenance of arterial-venous identity.